India’s Democratic Identity and Its Policy towards Myanmar from 1988 to 2010 - Htwe Hteik Tin Lwin (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2013)
Since the 1990s, India has reengaged with Myanmar government. The Indian government’s engagement with Myanmar’s military junta provoked a controversial issue in international community, claiming that ‘the oldest democratic country in Asia' is not doing enough to promote democracy in her neighborhood. The question raised was what has motivated India to develop cordial relations with Myanmar’s military junta. The paper emphasizes the role of India’s democratic identity in Indo-Myanmar policy during 1988-2010. Previous literatures revealed India’s policy towards Myanmar in economic and security assumptions. They tended to sketch India Policy as ‘in-active’ in promotion of democracy practiced from west democratic institutions norms, such as ‘isolation’ and ‘totally disengagement’. The paper briefly explains Indo-Myanmar relations from 1988 to 2010. Security and economic interests play a larger role than the intention to promote democratic identity in Myanmar. The paper argues that in the background of Indo-Myanmar development cooperation, India has made efforts to promote democratic value in Myanmar differently from other western democratic countries. Engagement policy has shaped Indo-Myanmar relations in the 1990s. India ‘engagement policy’, ‘non-isolation’ and ‘development cooperation’ with Myanmar government has brought up contractions.